Aplikasi Tutorial Resep Masakan Tradisional Aceh Berbasis Android Menggunakan Metode Analytical Hierarchy Process (AHP) - Rozzi Kesuma Dinata (UIN Sunan Kalijaga Yogyakarta, 2018)
Traditional Aceh cuisine is a dish cooked by the people of Aceh and marinade formulated by the people of Aceh. Based on the results of interviews with the community around the traditional dishes are often cooked every day such as